(untitled) (Alternautas, 2024)
Since 2008, there has been a notable increase in studies on processes of inclusion, retention and graduation of indigenous students in higher education in Latin America; a growing interest in research and university extension activities in collaboration with indigenous and Afro-descendant communities; and the establishment of intercultural academic spaces in the region. This article offers a literature review analysis of this field of study and intervention, elaborated in Spanish and Portuguese in the framework of Latin American institutions. This analysis identifies the various voices, analytical perspectives, lines of research, conceptual debates and contributions that enrich the understanding of some types of experiences in this field, often described as ’intercultural’, and others usually considered as educational inclusion of indigenous and Afro-descendant populations in the field of Higher Education in Latin America. The literature review reveals that much of this research is the result of collaborative work between diverse actors committed to promoting intercultural perspectives at the higher education level, and reflects the historical struggles sustained by these peoples as the fundamental structuring component of these experiences. It is concluded that the increase in research and interventions makes it plausible to postulate and describe the consolidation of a specific field of study and intervention for Latin America, which can be defined as ’Higher Education, Indigenous and Afro-descendant Peoples’ and that the experiences analysed reflect a particular and historical link between university systems and Indigenous and Afro-descendant Peoples in Latin America.